2021
DOI: 10.3389/fphys.2021.716877
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Method of Predicting Fractional Flow Reserve Based on Multiple Independent Risk Factors

Abstract: The use of diameter stenosis (DS), as revealed by coronary angiography, for predicting fractional flow reserve (FFR) usually results in a high error rate of detection. In this study, we investigated a method for predicting FFR in patients with coronary stenosis based on multiple independent risk factors. The aim of the study was to improve the accuracy of detection. First, we searched the existing literature to identify multiple independent risk factors and then calculated the corresponding odds ratios. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…ese emerging indicators have the advantages of simplicity, time savings, and no need to use adenosine. On the other hand, based on diameter stenosis determined by CAG, several clinical risk factors were also taken into account and significantly improved predictive accuracy [23]. Erdogan M et al suggested a systemic immune-inflammation index, calculated by neutrophil * platelets/lymphocytes, can predict the FFR ≤0.8, with 78.4% sensitivity and 64.0% specificity [7].…”
Section: Discussionmentioning
confidence: 99%
“…ese emerging indicators have the advantages of simplicity, time savings, and no need to use adenosine. On the other hand, based on diameter stenosis determined by CAG, several clinical risk factors were also taken into account and significantly improved predictive accuracy [23]. Erdogan M et al suggested a systemic immune-inflammation index, calculated by neutrophil * platelets/lymphocytes, can predict the FFR ≤0.8, with 78.4% sensitivity and 64.0% specificity [7].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of invasive FFR relied on three steps: 1) Adenosine (140 μg/kg/min) was administrated through intravenous infusion to induce maximum hyperemia of the coronary artery; 2) We obtained pressure waveforms of aortic pressure and distal arterial pressure using pressure wire measurement; 3) We further calculated the invasive FFR for the ratio of the mean pressure at a cross- Section 3 cm downstream of the stenosis (P d ) to the aortic pressure (P a ) at least three cardiac cycles ( Taylor et al, 2013 ; Zhang et al, 2021a ). Patient informed consent was waived due to the retrospective nature of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The blood flow state was steady, and the properties of the arterial walls were set to non-slip rigid ( Zhang et al, 2014 ). The density and viscosity of blood flow were set at 1,050 kg/m 3 and 0.0035 Pa s, respectively ( Zhang et al, 2021a ). The mesh of the coronary geometry model discretized the computational domain into tetrahedral elements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation